Persepsi Transferable Skills Guru Produktif Ditinjau dari Pengalaman Mengajar dan Pengalaman Pelatihan - Seno Isbiyantoro; Purnomo Purnomo; Anik Nur Handayani (Graduate School of Universitas Negeri Malang, 2019)
Abstract: This research was aimed to investigate (1) the influence of teaching experience and training experience with perceptions of transferable skills productive teachers; (2) the influence of teaching experience with perceptions of transferable skills productive teachers, (3) the influence of training experience with transferable skills productive teachers. The samples were 137 productive teachers of Computer and Information Engineering study programs in Malang city and regency and Batu city. To answer its problems, the study collected the data by using questionnaires. The data gathered were then analyzed employing desctiptive analysis, regression analysis, and partial correlation analysis. The study found that: (1) there is a significant influence on teaching experience and training experience with perceptions of transferable skills productive teachers (0,000 < 0,05); (2) there is a significant influence on teaching experience with perceptions of transferable skills productive teachers (0,001 < 0,05); (3) here is a significant influence on teaching experience with perceptions of transferable skills productive teachers (0,000 < 0,05).Abstrak: Penelitian ini bertujuan untuk mengetahui (1) pengaruh pengalaman mengajar dan pengalaman pelatihan dengan persepsi transferable skills guru produktif; (2) pengaruh pengalaman mengajar dengan persepsi transferable skills guru produktif; (3) pengaruh pengalaman pelatihan dengan transferable skills guru produktif. Penelitian ini menggunakan rancangan ex-postfacto. Sampel penelitian ini adalah 137 guru produktif program studi Teknik Komputer dan Informasi di kota dan kabupaten Malang serta kota Batu. Pengumpulan data menggunakan kuesioner. Analisis data pada penelitian ini menggunakan analisis deskriptif, analisis regresi ganda, dan analisis korelasi parsial. Hasil penelitian ini adalah (1) ada pengaruh signifikan pengalaman mengajar dan pengalaman pelatihan dengan persepsi transferable skills guru produktif (0,000 < 0,05); (2) ada pengaruh signifikan pengalaman mengajar dengan persepsi transferable skills guru produktif (0,001 < 0,05); (3) ada pengaruh signifikan pengalaman pelatihan dengan persepsi transferable skills guru produktif (0,000 < 0,05).